2021
DOI: 10.21037/tlcr-21-960
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of perioperative outcomes of robotic-assisted versus video-assisted thoracoscopic right upper lobectomy in non-small cell lung cancer

Abstract: Background: Robotic-assisted thoracic surgery (RATS) has been widely used in the treatment of lung cancer.The perioperative outcomes of right upper lobectomy (RUL) using RATS and video-assisted thoracic surgery (VATS) were retrospectively investigated and compared. We aimed to summarize a single-center experience of RATS and 4-port unidirectional VATS in RUL, and to discuss the safety and the essentials of the surgery. Methods:We retrospectively analyzed the 685 with non-small cell lung cancer (NSCLC) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 20 publications
4
31
0
Order By: Relevance
“…The dissection of LNs is of key importance in the surgical resection of NSCLC. Similar to the results reported by previous studies that enrolled younger patients, the total number of LNs harvested by RATS was 12.01 ± 5.55 in our study, suggesting that LNs dissection using robot-assisted surgical systems may not be significantly affected by growth in ages (11,15,30,31 Although various kinds of preoperative LNs assessment approaches have been prompted, there is still a 3%-15% of rate occult N2 disease identified at the pathological stage (11, 32, 37-40). However, the occult N2 disease could lead to a poor prognosis and therefore influence the survival profiles in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The dissection of LNs is of key importance in the surgical resection of NSCLC. Similar to the results reported by previous studies that enrolled younger patients, the total number of LNs harvested by RATS was 12.01 ± 5.55 in our study, suggesting that LNs dissection using robot-assisted surgical systems may not be significantly affected by growth in ages (11,15,30,31 Although various kinds of preoperative LNs assessment approaches have been prompted, there is still a 3%-15% of rate occult N2 disease identified at the pathological stage (11, 32, 37-40). However, the occult N2 disease could lead to a poor prognosis and therefore influence the survival profiles in our study.…”
Section: Discussionsupporting
confidence: 91%
“…RATS, VATS, and OL were conducted according to the procedures described previously (6,14,15). Briefly, patients received general anesthesia with double-lumen tracheal intubation and contralateral single-lung ventilation and underwent radical pulmonary lobectomy combined with systemic pulmonary and mediastinal LNs dissection.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The best surgical option for resectable stage II and above NSCLC is still controversial, and studies generally agree that thoracotomy can achieve excellent long-term postoperative outcomes, especially in lymph node dissection (13,19). It has been reported recently that RATS has the same long-term outcomes as thoracotomy and VATS, as well as better short-term results (20)(21)(22)(23)(24). The ROMAN study (7) and RVlob Trial (25), which is a perioperative randomized multicentric clinical trial for stage I-II NSCLC, both confirmed that robotic methods can improve lymph node staging and obtain a higher lymph node yield.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al discovered that for patients with cN2 non-small cell lung cancer (NSCLC) RATS has similar long time survival to thoracotomy ( 12 ). Compared to VATS, RATS is able to dissect lymph nodes more finely and has a relatively shorter operation time ( 13 ).…”
Section: Discussionmentioning
confidence: 99%